EVALUASI PERLAKUAN AKUNTANSI ASET TETAP PADA CV SARANA ADI PUTRA PERIODE 2017 s/d 2018 - asmara, fany; Agustina, Yumniati (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2020)
The purpose of this study is to evaluate the accounting treatment of fixed assets in CV Sarana Adi Putra by using descriptive qualitative methods. This study refers to SAK ETAP Chapter 15 concerning fixed assets that apply in Indonesia. With the evaluation results of this study it can be concluded in terms of recognition of fixed assets are recognized if the fixed assets have been used as operational which is in accordance with SAK ETAP, and the acquisition of fixed assets is not in accordance with SAK ETAP because the company only records the purchase price, and costs incurred are directly charged . In terms of measurement of fixed assets, it is not in accordance with SAK ETAP because there is no policy governing the valuation. In terms of the methods of preparation, the company uses the straight-line method in accordance with SAK ETAP. In terms of the presentation of fixed assets, the company records acquisition costs, depreciation expense, accumulated depreciation, book value in which the accumulated depreciation is reduced according to SAK ETAP. in terms of disclosure of fixed assets, is not in accordance with SAK ETAP because there is no policy governing the disclosure. Keywords: Fixed Assets, SAK ETAP Chapter 15 concerning Fixed Assets